The final solution : a genocide - Bloxham, Donald 1973- (Oxford histories, 2009)
"The Holocaust is frequently depicted in isolation by its historians. Some of them believe that to place it in any kind of comparative context risks diminishing its uniqueness and even detracts from the enormity of the Nazi crime. In reality, such a restricted understanding of 'uniqueness' has pulled the Holocaust apart from history and set up barriers to a better understanding of the racial onslaught unleashed within the Third Reich and its conquered territories." "Working against the grain of much earlier writing, this innovative new history combines a detailed re-appraisal of the development of the genocide of the Jews, a full consideration of Nazi policies against other population groups, and a comparative analysis of other modern genocides."--BOOK JACKET